KEMAMPUAN PROFESIONAL GURU BIDANG STUDI PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN PRESTASI BELAJAR SISWA SDN 1 SIMPANG PEUT NAGAN RAYA - Eka Agusniar (Universitas Islam Negeri Ar-Raniry, 2015)
Professional teachers are teachers who have ability to design, implement, evaluate teaching learning and also have a high responsibility to improve students’ achievement. This study aims to know the ability of professional teacher of islamic education to improve students’ achievement at elementary school, SDN 1 Simpang Peut, Kuala district, Nagan Raya regency. The result showed that most of islamic education teachers of SDN 1 Simpang Peut had weaknesses in lesson planning. In general, islamic education teachers of SDN 1 Simpang Peut Nagan Raya had good ability to implement the lesson. It can be seen from their classroom management, learning facilities, teaching learning implementation, and interaction in the class. Yet, the comprehension of islamic education teachers toward the use of instructional media was still very limited. Half of islamic education teachers at SDN1 Simpang Peut, Kuala distric, Nagan Raya regency have good ability in evaluating the instruction. It can be seen from the item test produced by teachers to improve students’ achievement.